2009
DOI: 10.1175/2008jamc1871.1
|View full text |Cite
|
Sign up to set email alerts
|

On the Relationship between North Atlantic Sea Surface Temperatures and U.S. Hurricane Landfall Risk

Abstract: In the recent literature, considerable attention has been paid to the relationship between climate signals and tropical cyclone activity. Much of the research has focused on Atlantic Ocean basin activity while less attention has been given to landfall frequency and the geographic distribution of risk to life and property. However, recent active seasons like 2004 and 2005 and the resulting damage and economic loss have generated significant interest in the relationship between climate and landfall risk. This st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 43 publications
(33 reference statements)
0
17
0
Order By: Relevance
“…In China, about 60% of the population live in coastal areas and this proportion rises to more than 80% for Japan where no one is living more than 120 km from a coast [Hinrichsen, 1999]. While studies suggested that higher sea surface temperatures could result in more destructive TCs [Webster et al, 2005;Emanuel, 2005a;Dailey et al, 2009;Knutson et al, 2010;Vecchi, 2012a, 2013], model projections provided conflicting trends for TC frequency and different long-term predictions with respect to the region considered [Knutson et al, 2010;Mendelsohn et al, 2012]. Once the subject of intense debate within the scientific community [Emanuel, 2005a[Emanuel, , 2005bLandsea, 2005;Pielke, 2005], recent studies have confirmed an upward trend in TC activity for the Atlantic basin while no similar trends were found for the other TC basins throughout the world [Kossin et al, 2007;Vecchi, 2012b, 2013].…”
Section: Introductionmentioning
confidence: 99%
“…In China, about 60% of the population live in coastal areas and this proportion rises to more than 80% for Japan where no one is living more than 120 km from a coast [Hinrichsen, 1999]. While studies suggested that higher sea surface temperatures could result in more destructive TCs [Webster et al, 2005;Emanuel, 2005a;Dailey et al, 2009;Knutson et al, 2010;Vecchi, 2012a, 2013], model projections provided conflicting trends for TC frequency and different long-term predictions with respect to the region considered [Knutson et al, 2010;Mendelsohn et al, 2012]. Once the subject of intense debate within the scientific community [Emanuel, 2005a[Emanuel, , 2005bLandsea, 2005;Pielke, 2005], recent studies have confirmed an upward trend in TC activity for the Atlantic basin while no similar trends were found for the other TC basins throughout the world [Kossin et al, 2007;Vecchi, 2012b, 2013].…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, additional moisture transport by the TC is favourable to enhanced precipitation but does not guarantee it. Hurricane Hugo in 1989 made landfall in South Carolina causing around one billion dollars of damage by its strong winds, but only produced modest rainfall (Konrad and Perry 2009;Cline 2002). On the other hand, not every heavy rainfall coinciding with TCs can be attributed to TCs (Konrad and Perry 2009;Schumacher and Galarneau 2012).…”
Section: Relationship With Tc Precipitationmentioning
confidence: 99%
“…We select the US North Atlantic coast to evaluate Delft3D model parameter sensitivity because this region is somewhat reliant on numerical simulations for accurate hurricane hazard estimates. Historical hurricane tracks show few landfalling hurricanes of significant strength within the region (Dailey et al, 2009;AOML, 2015) and few coastal surge observations at tidal stations (NOAA, 2015b). A qualitative review of this empirical evidence may imply that hurricane storm surge is not a concern; however, recent research suggests that analysis using only empirical surge and hurricane parameter records is, at best, inconclusive.…”
Section: North Atlantic Storm Surgementioning
confidence: 99%